96.3k views
1 vote
Why does the n+1 and (1-n) cancel out?


4 {}^(n + 1) * 4 {}^(1 - n) * 4 {}^(2) \\ = 4 {}^(n + 1 + (1 - n) + 2) \\ = 4 {}^(4) \\ = 256


User Ifau
by
4.9k points

1 Answer

11 votes

The rule being used is
a^b*a^c = a^(b+c)

You add the exponents when multiplying exponentials like this with the same base.

The n+1 adds with 1-n so that the n terms cancel out

n+(-n) = n-n = 0n = 0

The '1's dont cancel out though.

User Duncan Beevers
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.